Implementation of Three-Phase Bidirectional Isolated DC-DC Converter with Improved Light-Load Efficiency - Sharifuddin N.S.M.; Tan N.M.L.; Toh C.L.; Ramli A.Q. (Institute of Electrical and Electronics Engineers Inc., 2023)
Efficiency; Modulation; Bidirectional isolated dc-dc converter; Burst-mode; Dual active bridges; Efficiency improvement; Intermittent switching; Light-load efficiency; Light-load efficiency improvement; Phase shift modulation; Three phase; Three phasis; Three-phase bidirectional isolated dc-dc converter; Three-phase dual-active bridge; DC-DC converters